Implementation of the Pemuda Tangguh Scholarship Program for Students in Supporting Education in Surabaya City - Salam, Muhammad Nur; Arif, Lukman (PT FORMOSA CENDEKIA GLOBAL, 2024)
The research aims to evaluate the implementation of the Pemuda Tangguh Scholarship Program in supporting education for students in Surabaya. It uses a qualitative descriptive approach, collecting data through observation, interviews, and documentation. Data analysis involves techniques like data condensation, data display, and drawing conclusions. The findings show that the program aligns well with its target group, the implementing organization, and the target group with the organization, indicating successful implementation. However, there are inconsistencies between regulations and distributed pamphlets, and students express the need for additional financial support for daily expenses.